Money laundering as a form of economic criminality – The case of the Republic of Kosovo - Ceku, Orhan Maxhun; Kutllovci, Sheqir; Emini, Ardian; Nimani, Petrit (International Journal of Management Excellence (ISSN: 2292-1648), 2019)
Economic criminality is a criminal activity that violates the economic and property values of the state, harms the public budget, and causes losses to economic entities, harms society in general. Combating and preventing this criminal activity that takes on transnational crime dimensions requires repressive legislation and international cooperation of sovereign states. Republic of Kosovo is assessed as a country that has largely expressed the phenomenon of economic criminality, in particular, money laundering, corruption, tax evasion, trafficking in human beings and as a transit country of drug trafficking.This paper addresses the legislation that prevents and fights the criminal offense of money laundering in the Republic of Kosovo. The paper also includes international instruments that regulate the fight against money laundering. The negative effects of the criminal offense of money laundering appear to be more pronounced in small countries and with non-consolidated democracies such as Kosovo. Kosovo's legislation has been continuously adapted to the conditions and circumstances by taking the pattern of EU legislation and international conventions of the UN system.